Retrospective Comparison of the Supported and Unsupported Bovine Jugular Vein Conduit in Children - Lueth, Erin T; Gist, Katja M; Burkett, Dale A; Landeck, Bruce F; Brinton, John T; Meier, Maxene R; Coffin, Jessica M; Schafer, Michal; Jaggers, James; Mitchell, Max B (The Annals of thoracic surgery, 2019)
Bovine jugular vein (BJV) conduits are commonly used for pulmonary valve replacement in pediatric patients. They are available in supported (sBJV) and unsupported (uBJV) versions. The purpose of this study was to compare outcomes of sBJV and uBJV conduits. In this single-center retrospective review of patients younger than 18 years undergoing BJV placement (2009 to 2017), blinded cardiologists reviewed postoperative 6-, 12-, 24-, 36-month, and the most recent echocardiogram before any valve-related event or death. Outcomes assessed included conduit stenosis (m/s), regurgitation (none to mild vs moderate to severe) and right ventricular function (normal vs abnormal). Cox proportional models and Kaplan-Meier analyses were performed. BJV conduits (N = 109) were placed (39 supported, 70 unsupported) in 101 patients. Patient characteristics and conduit size were not different between cohorts. sBJV had more stenosis at 6 and 12 months (p = 0.02 and p = 0.03), but V in both groups was mild (≤2 m/s). A greater proportion of uBJV had moderate to severe regurgitation at 12 months compared with sBJV (p = 0.03). Right ventricular function did not differ at any time point. On last follow-up echocardiogram, sBJV conduits had higher gradients (p = 0.01). This was not associated with increased intervention or replacement. Freedom from replacement or intervention did not differ between valve types (median follow-up, 3.6 years). There was a 9% incidence of endocarditis at median follow-up 2.4 years. Seventy percent of cases with endocarditis were managed medically. There were no clinically significant echocardiographic or outcome differences between sBJV and uBJV conduits. We identified a relatively high incidence of endocarditis, which is consistent with prior reports.